Habilidades e estratégias para gerir a ansiedade antes e durante o recital: um estudo multicaso com pianistas estudantes e profissionais - Mendes, Dayse Christina Gomes da Silva (2014)
The general objective of this research consists to investigate the performance abilities and strategies used by pianists to manage anxiety at presentations. The specific objectives being to realize a comparative study among professionals and students in their activities to prepare and presentation for a recital; investigate the behavioral perception that pianists have of themselves as performers; examine the trajectory of preparation for the recital in the ten weeks preceding the day of the presentation; analyze the factors that influence the performance of the pianist on stage; examine whether participants had anxiety and identify the symptoms present before and during the recital; verify the relationship between the environment in preparation for the public presentation and management of anxiety; verify the factors that influenced the concentration during the recital. The process for construction of theoretical reference consists of five thematic ramifications, these being: anxiety, preparation for recital, concentration, abilities and strategies, which converge to embase knowledge concerning the phenomena of preparing for a performance. The methodology brought to light a case study, of the multicase type, participants of which are students and professionals in Recife, Pernambuco, Brazil, which were classified as Group 1): three piano students at Escola Técnica Estadual de Criatividade Musical (ETECM) (State Technical School of Music Creativity) and, Group 2): three professional pianists, all of them in the stage of preparation for a recital. Field data collected were semistructured interview before and after recitals, questionaire concerning behaviour and anxiety, study sequence routines, and audio register of recitals. This research lies in the area of music education, but is anchored in music psychology, which is the study of how persons perceive, learn, remember something, and reflect on information received, with the objective of comprehending the mental processes concerning a variety of musical behaviour patterns, and analyze the influence social surroundings exert on musical conduct. The analyses and results of data consisted of three parts which followed these steps: 1) discovery and analysis of the abilities and strategies used before and during the presentation to control anxiety, 2) comprehension of the perception of behaviour that pianists had of themselves during the days preceding the presentation and perception of anxiety symptoms before and during performance, 3) qualitative evaluation of results. It is inferred that not only students, but also professionals presented efficient abilities and strategies to reach their objective, with a minimum of anxiety. These aspects, however, exist on different levels of knowledge and cognitive development, and are analyzed according to the three stages to acquire abilities, and by the matrix of cognitive-musical ability.